Structural and Drug Screening Analysis of the Non-structural Proteins of Severe Acute Respiratory Syndrome Coronavirus 2 Virus Extracted From Indian Coronavirus Disease 2019 Patients - Biswas, Nupur; Kumar, Krishna; Mallick, Priyanka; Das, Subhrangshu; Kamal, Izaz Monir; Bose, Sarpita; Choudhury, Anindita; Chakrabarti, Saikat (Frontiers in Genetics, 2021)
The novel coronavirus 2 (nCoV2) outbreaks took place in December 2019 in Wuhan city, Hubei province, China. It continued to spread worldwide in an unprecedented manner bringing the whole world to a lockdown and causing severe loss of life and economic stability. The COVID- 19 pandemic has also affected India infecting more than 10 million till 31st December 2020 and resulting in more than a hundred thousand deaths. In absence of an effective vaccine, it is imperative to understand the phenotypic outcome of the genetic variants and subsequently the mode of action of its proteins with respect to human proteins and other bio-molecules. Availability of a large number of genomic and mutational data extracted from the nCoV2 virus infecting Indian patients in public repository provided an opportunity to understand and analyze the specific variations of the virus in India and their impact in broader perspectives. Non-structural proteins of the SARS-CoV2 virus play a major role in its survival as well as virulence power. Here, we provide a detailed overview of the SARS-CoV2 non-structural proteins (NSPs) including primary and secondary structural information, mutational frequency of the Indian and Wuhan variants, phylogenetic profiles, three dimensional (3D) structural perspectives using homology modeling and molecular dynamics analyses for wild type and selected variants, host- interactome analysis and viral-host protein complexes, and in silico drug screening with known antivirals and other drugs against the SARS-CoV2 non-structural proteins isolated from the variants found within Indian patients across various regions of the country. All this information are categorized in the form of a database named, Database of Non-Structural Proteins of India specific Novel Coronavirus (DbNSP InC), which is freely available at http://www.hpppi.iicb.res.in/covid19/index.php.